Strategic Management of Project-Based Learning (PjBL) for Enhancing Religious Character Development Among High School Students - Feri Firmansyah Athori; Basnang Said (Jurnal Iman dan Spiritualitas, 2026)
The implementation of the Project-Based Learning (PjBL) model at SMA Negeri 1 Ciracap and SMA Negeri 1 Surade, Sukabumi Regency, West Java, plays a crucial role in shaping students' religious character. This study aims to explain how PjBL management is implemented as a strategy for strengthening religious values in the Islamic Religious Education learning process. Using a qualitative descriptive case study approach, data were collected through in-depth interviews, observations, and documentation with Islamic Religious Education teachers, principals, and students. The results show that project planning was systematically structured by integrating spiritual values, such as digital da'wah materials, social and religious practices, and moral strengthening. Teachers acted as facilitators, guiding students to be responsible, collaborate, and relate each project to Islamic teachings. The evaluation process was comprehensive, not only assessing the final product but also evaluating the learning process, spiritual goals, and changes in students' religious behavior. The applied management emphasized active collaboration between teachers, students, and the school to create a religious, participatory, and character-building learning culture. In line with the Pancasila Student Profile, this study concludes that effective PjBL management is an innovative approach to improving students' religious character and providing practical guidance for Islamic Religious Education educators and school policymakers in developing a curriculum that balances academic, moral, and spiritual aspects.